From Sentence to Short Paragraphs : Developing Writing Tasks for Beginner Learners - Luciana Luciana; Zaitun Qamariah; Novia Fitrian; Tria Angela Kusumaningrum (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research explores strategies to support novice learners in developing their writing skills in the English Education Study Program at an Indonesian university, the Islamic Institut of Palangka Raya. Writing is often considered one of the most challenging aspects of language learning, requiring a combination of vocabulary knowledge, grammatical precision and structural coherence. The participants, five beginner learners, were selected using purposive sampling and underwent a writing task that progressed from sentence-level exercises to paragraph construction. Data were collected through semi-structured interviews and direct observation, and analyzed thematically. Findings showed that challenges such as limited vocabulary, grammatical errors, and psychological barriers such as low self-confidence hindered students' progress. Effective strategies included guided sentence construction, collaborative writing exercises, and exposure to structured templates and quality reading materials. The participants reported improved confidence and skills through positive feedback and step-by-step writing tasks. The findings suggest that integrating motivating and structured learning methods can significantly improve writing ability among beginners, contributing to their academic and personal growth.